2010
DOI: 10.1007/s00261-010-9618-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidental pancreatic cysts on 3D turbo spin echo magnetic resonance cholangiopancreatography: prevalence and relation with clinical and imaging features

Abstract: Incidental pancreatic cysts represent a frequent finding at MRCP, correlating positively with increasing age, and negatively with biliary autoimmune disease. Cysts more frequently present with IPMN-like pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 24 publications
4
67
0
5
Order By: Relevance
“…Currently, the real prevalence of PCLs remains unknown. Several studies have attempted to elucidate this matter, resulting in a wide spectrum of prevalence estimates ranging from 0.2% to 44.7% (1)(2)(3)(4). This wide range is a consequence of significant heterogeneity with regard to the selected population, the type of imaging technique or the subtype of cysts described.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the real prevalence of PCLs remains unknown. Several studies have attempted to elucidate this matter, resulting in a wide spectrum of prevalence estimates ranging from 0.2% to 44.7% (1)(2)(3)(4). This wide range is a consequence of significant heterogeneity with regard to the selected population, the type of imaging technique or the subtype of cysts described.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of pancreatic cysts within the population ranges from 2.6% to as high as 44.7% worldwide (1)(2)(3)(4), and a study from Japan reported that 24.3% of the population has pancreatic cysts based on autopsy cases. However, an accurate differential diagnosis of cystic pancreatic lesions remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…IPMN comprises main duct type (MD‐IPMN), branch duct type (BD‐IPMN), and mixed type (MD + BD). MD‐IPMN more frequently progresses to malignant lesions (60‐70%)2, 5, 6, 7 than BD‐IPMN,2, 5, 8 although BD‐IPMN is more commonly seen than MD‐IPMN 9, 10. Researchers have also hypothesized that benign BD‐IPMN may develop distinct pancreatic ductal adenocarcinoma (PDAC) synchronously or metachronously.…”
Section: Introductionmentioning
confidence: 99%